Paper Dolls: Medicine, Play, and Shibata Kōichi’s Obstetric Phantoms - Whiteley, Rebecca (Material Culture Review / Revue de la culture matérielle, 2024)
This article addresses the striking resemblance of a late nineteenth-century obstetrical simulator to contemporary commercial paper dolls. This period is often characterised in histories of medicine as one of increasing institutionalisation and professionalisation of childbirth through hospital training and state regulation. But this narrative is only part of the story. It marginalises the perspective of patients and midwives, and those outside of the geographic ‘West’, and it silences aspects of medical culture: social and caring relationships, emotion, play, and humour. While these aspects of medical history are less well represented in textual sources, material objects like Shibata Kōichi’s ‘Obstetrical Pocket-Phantoms’ can help to give a fuller picture.Beginning by situating Shibata’s phantoms in the conventional histories of obstetric training and the intermedial spaces of the clinic and lecture theatre, I then ask how the phantoms might have been used and understood differently outside of these spaces. Using Robin Bernstein’s concept of ‘scriptive things’, I employ a visual and material study of the objects, informed by the wider cultural contexts of dolls and popular print culture in Germany, the USA and Japan, to argue for a history of Shibata’s phantoms as paper dolls that encouraged many forms of play: from learning and explorative, to mothering and caring, to humorous and subversive. By acknowledging that Shibata’s phantoms would also have been recognised as paper dolls, I present a history that centres unrecorded aspects of, and under-studied agents in, medical culture.